2009
DOI: 10.1080/13803390802595568
|View full text |Cite
|
Sign up to set email alerts
|

Detection of visuoperceptual deficits in preclinical and mild Alzheimer's disease

Abstract: Exhaustive neuropsychological assessment of mild cognitive impairment (MCI) subjects frequently identifies cognitive deficits other than memory. However, visuoperception has rarely been investigated in MCI. The 15-Objects Test (15-OT), a visual discrimination task based on the Poppelreuter Test, consists of 15 overlapping objects. Poppelreuter-type tests are frequently used to detect visual agnosia. However, more complex tests, such as the 15-OT, are required to detect visuoperceptual signs in those patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 32 publications
4
48
0
2
Order By: Relevance
“…The test battery includes common neuropsychological instruments whose utility have been demonstrated in research studies. In addition, we used the 15-Objects Test because it is easy to administer and provides information regarding the overall severity of cognitive impairment and visual perception abilities (Alegret et al, 2009; Alegret et al, 2010). We report here the psychometric characteristics of these tests, as well as the normative ranges and percentile scores for specific age and/or education subgroups.…”
mentioning
confidence: 99%
“…The test battery includes common neuropsychological instruments whose utility have been demonstrated in research studies. In addition, we used the 15-Objects Test because it is easy to administer and provides information regarding the overall severity of cognitive impairment and visual perception abilities (Alegret et al, 2009; Alegret et al, 2010). We report here the psychometric characteristics of these tests, as well as the normative ranges and percentile scores for specific age and/or education subgroups.…”
mentioning
confidence: 99%
“…MCI patients who later convert to Alzheimer's disease show damage to the MTL (Bell-McGinty et al, 2005), including to the PRC (Mitchell et al, 2002). Interestingly, evidence suggests that MCI and Alzheimer's disease patients show impairments on perceptual tasks, especially when those tasks require complex visuoperceptual processing of objects (e.g., Alegret et al, 2009Alegret et al, , 2010. Alegret et al found that MCI and Alzheimer's disease patients have visuoperceptual deficits that may be more subtle than standard visuoperceptual tests can pick up, yet no study The representational-hierarchical theory.…”
Section: Introductionmentioning
confidence: 99%
“…None of the patients exhibited significant global-related activation within the borders of the TPA region. Without correction for multiple comparisons (p B 0.05 uncorrected) global-related cortical activation was observed in one patient within a parietal region located laterally and anterior to the known TPA (62, 37,34). In one patient, there was no global-or local-related activation, while for the other three patients, activity in the temporoparietal area was greater when attending the local versus the global attributes of the Navon letters.…”
Section: Cortical Activation Corresponds To the Behavioral Deficits Smentioning
confidence: 97%
“…Compared with adult norms, patients had lower results on the Hooper test (9.5 ± 7.58 items were recognized vs. adult norms of 15.75 ± 5.89 [36]); the Gollin visual closure test (3.29 ± 1.44 attributes needed to identify the object vs. average adult norms of 1.95 ± 0.62 [16]); and the ''15 Object Test'' of overlapping figures (5.71 ± 4.16 different items were recognized in a tangled image vs. average adult norms of 13.82 ± 1.08 [37]). In this test, patients tended to focus on a local attribute resulting in misidentification of the entire object (see example in Fig.…”
Section: Routine Visual Functions Revealed Impaired Peripheral Visualmentioning
confidence: 99%